Caracterização da capacidade patogênica de Trypanosoma cruzi isolado em Arequipa - área endêmica do Peru - Edward Valencia Ayala (2017)
Trypanosoma cruzi is a complex and heterogeneous parasite, formed by six phylogenetic groups, DTU TcI to TcVI, which have great intraspecific variation, presenting different blood forms, pathogenicity, drug sensitivity, and antigenic profile, among other characteristics. In this work, we evaluated the infective or invasive capacity and antioxidant defense of a "La Joya" isolate, a region located in the west of the city of Arequipa, Peru, identified in the present work as DTU TcI. Our in vitro and in vivo experiments were carried out in a comparative perspective with Colombiana strain (DTU TcI), a virulent strain, and with CL Brener (DTU TcVI) also considered as a virulent clone of the parasite. The analysis of the proliferative capacity of each strain in in vitro infections of peritoneal macrophages obtained from BALB/c mice showed that Arequipa strain was the least infective, presenting lower rates of infection and multiplication when compared to Colombiana and CL Brener. Macrophage effectors responses were analyzed and the results showed that Arequipa strain induces higher percentages of the oxidant molecules EROs and NO when compared to Colombiana and CL Brener. The evaluation of the expression of the parasite antioxidant enzymes TcAPX, TcCPX, TcMPX, TcTrS, TcTrR, TcSodA and TcSodB in in vitro infection of macrophages showed lower levels of TcMPX, TcTrR, TcSrA, TcSodA and TcSodB by Arequipa in the initial time points when compared to the other two strains. After several attempts, infection of C57BL/6 mice with Arequipa strain was unsuccessful. This strain was then reactivated (Arequipa-RE) through triatomine passages resulting in increased expression of TcTrS, TcAPX, TcMPX and TcCPX enzymes in the first hours after in vitro macrophages infection, compared to the non-infective Arequipa. We also evaluated the experimental infections of C57BL/6 mice with each strain. The results showed that Arequipa-RE strain presented similar levels of parasitemia and tecidual parasitism as Colombiana strain, with a predominant tropism to heart and colon, although Arequipa-RE had a lower tissue parasitism compared to the Colombiana strain. CL Brener clone presented higher levels of parasitemia, mortality, and tissue parasitism in relation to the other two strains, and cardiac and skeletal muscle tropism. The evaluation of the proinflammatory cytokines INF-γ, TNF-α and IL-12 and anti-inflammatory IL-10 in the cardiac tissue of infected mice showed early induction in the synthesis of all the cytokines evaluated in the strain Arequipa infection, when compared with Colombiana and CL Brener. Our results therefore indicate low in vitro and in vivo infectivity of the Arequipa strain, with rapid immunological control of parasite replication and modulation of the immune response.